2019
DOI: 10.1038/s41598-019-44575-8
|View full text |Cite
|
Sign up to set email alerts
|

Variable osteogenic performance of MC3T3-E1 subclones impacts their utility as models of osteoblast biology

Abstract: The spontaneously immortalized murine calvarial cell line MC3T3-E1 and its derivative subclones are widely used models of osteoblast biology. Many investigators have reported conflicting data under seemingly similar experimental conditions, though the specific subclone studied is often not specified. The purpose of this study was to directly compare the commercially available MC3T3-E1 subclones 4, 14, and 24 in terms of responsiveness to osteogenic induction media and/or stimulation with rhPTH[1–34]. We assaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…By applying a similar screening strategy using 42 Swiss 3T3 fibroblast subclones, Zfp423 was found to be a novel adipocyte differentiation regulator and adipocyte precursor cell marker 20 . In another study on osteoblast lineage, 15 subclones were established from the MC3T3-E1 osteoblast precursor 21 , and their osteogenic potential was analyzed in detail 22 . In addition, using a microarray approach of single CFU-F derived cells from human PDL, dental pulp, and bone marrow, Menicanin et al found a common gene profile in high growth/multi-potential cells when compared with low growth cells 23 .…”
Section: Discussionmentioning
confidence: 99%
“…By applying a similar screening strategy using 42 Swiss 3T3 fibroblast subclones, Zfp423 was found to be a novel adipocyte differentiation regulator and adipocyte precursor cell marker 20 . In another study on osteoblast lineage, 15 subclones were established from the MC3T3-E1 osteoblast precursor 21 , and their osteogenic potential was analyzed in detail 22 . In addition, using a microarray approach of single CFU-F derived cells from human PDL, dental pulp, and bone marrow, Menicanin et al found a common gene profile in high growth/multi-potential cells when compared with low growth cells 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies used the murine calvarial pre-osteoblast cell line MC3T3-E1 [44,47,50]. Although these cells are widely used in material research, a recent study suggests that the performance of these cells might be different in the different subclones [59]. Two studies used primary cells isolated from rat calvaria [48,49], and one study used mesenchymal stem cells derived osteoblasts [42].…”
Section: Discussionmentioning
confidence: 99%
“…MC3T3-E1 and its derivatives are widely used tools in bone research, having been cited over 4000 times since their introduction in 1981. They express osteogenic gene expression, matrix deposition, and mineralization and can differentiate into mature osteoblasts [ 15 ].…”
Section: Methodsmentioning
confidence: 99%